Contributions of Stereopsis and Aviation Experience to Simulated Rotary Wing Altitude Estimation. (August 2020) - Hartle, Brittney; Sudhama, Aishwarya; Deas, Lesley M.; Allison, Robert S.; Irving, Elizabeth L.; Glaholt, Mackenzie G.; Wilcox, Laurie M.
Objective: We examined the contribution of binocular vision and experience to performance on a simulated helicopter flight task. Background: Although there is a long history of research on the role of binocular vision and stereopsis in aviation, there is no consensus on its operational relevance. This work addresses this using a naturalistic task in a virtual environment. Method: Four high-resolution stereoscopic terrain types were viewed monocularly and binocularly. In separate experiments, we evaluated performance of undergraduate students and military aircrew on a simulated low hover altitude judgment task. Observers were asked to judge the distance between a virtual helicopter skid and the ground plane. Results: Our results show that for both groups, altitude judgments are more accurate in the binocular viewing condition than in the monocular condition. However, in the monocular condition, aircrew were more accurate than undergraduate observers in estimating height of the skid above the ground. Conclusion: At simulated altitudes of 5 ft (1.5 m) or less, binocular vision provides a significant advantage for estimation of the depth separation between the landing skid and the ground, regardless of relevant operational experience. However, when binocular cues are unavailable aircrew outperform undergraduate observers, a result that likely reflects the impact of training on the ability to interpret monocular depth cues.